Tocilizumab has no direct effect on cell lines infected with human T-cell leukemia virus type 1 - Endo, Yushiro (J Int Med Res, 2021)
OBJECTIVE: It remains unclear whether human T-cell leukemia virus type 1 (HTLV-1) infection influences therapeutic responses in patients with rheumatic diseases and whether immunosuppressive treatments increase the risk of HTLV-1-related complications in HTLV-1 carriers with rheumatic diseases. We examined the effects of tocilizumab (TCZ), an interleukin (IL)-6 receptor antagonist, on two HTLV-1-infected T-cell lines (HCT-5 and MT-2) in vitro. METHODS: We evaluated production of cytokines and chemokines, expression of HTLV-I associated genes, HTLV-1 proviral load (PVL), expression of HTLV-1 structural proteins, and apoptosis. RESULTS: There were no significant differences in cytokine and chemokine levels in the culture supernatants of HCT-5 and MT-2 cells treated with phosphate-buffered saline (PBS) or TCZ. No significant differences were detected in mRNA abundance of Tax or HBZ, PVL, expression of the HTLV-1 structural protein GAG, or apoptosis among HCT-5 and MT-2 cells treated with PBS or TCZ. CONCLUSIONS: TCZ had no effect the cytokine profiles, HTLV-1 gene and protein expression, PVL, or apoptosis in HTLV-1-infected T-cell lines. Thus, TCZ treatment has no effect on HTLV-1 infection in vitro.